Ethics and Budget Allocation Decisions of Municipal Budget Officers - Reck, Jacqueline L. (Journal of business ethics, 2000)
The purpose of this study is to extend research which has looked at moral judgment. Specifically, the study examines the impact of moral judgment on the budget allocations made by government budget officers. Additionally, and as a result of previous research findings, the study looks at the relationship between political ideology, gender, age, profession and moral judgment., Results support prior research which has found an association between political ideology and moral judgment, and between gender and moral judgment.There was no indication that the level of moral judgment among accountants is different from that of other individuals serving as budget officers, or that age is significantly related to moral judgment. Additionally, the study finds that an individual's level of moral judgment has less of an impact on the individual's actions than does political ideology. Study results contribute to an understanding of the relationship of moral judgment to accounting, and the relationship of moral judgment to behavior. The study also adds to research into the relationship of political ideology and moral judgment.